MGIMO-UNIVERSITY IN GO TO THINK TANKS 2015 RANKING: GLOBAL TRENDS, LOCAL RESPONSES - M. V. Kharkevich (Vestnik MGIMO-Universiteta, 2016)
The article discusses the latest issue of Go to think tank ranking and MGIMO position in it. It also considers global trends related to changes in the environment and forms of activities of research centers, identified by the ranking. In particular, it notes the changes in the system of financing think tanks from the few large grants for an extended period of time to a small but numerous grants for short periods for specific projects. It also notes the increasing state pressure on think tanks from around the world. In addition, it points to increased competition on the market of ideas and scientific expertise. Research centers have to adapt to these changes. In view of these trends the experience of one of the research centers of MGIMO, the Center for Military-Political Studies is considered. Innovation activities of the Centre on a whole corresponds to global trends. The center is seeking to diversify its sources of funding and enhances the focus of research topics - long-term forecasting of the international military and political relations.